Juridical Problematics Of Business Use Rights Over Management Rights - Pradipa Probondaru, Ignatius (Faculty of Law, Universitas Pekalongan, 2024)
Cultivation rights according to the UUPA are granted on state land, but in its current development cultivation rights can be granted on state land and land with management rights. Management rights as control rights from the state, the authority to implement which is partly delegated to the holder of management rights, in the development of regulations can be granted on state land and customary land. The purpose of this writing is to describe the juridical problems of cultivation rights over management rights. The method used is normative legal research with priority on secondary data which is analyzed qualitatively. Inconsistencies occur between PP No. 18 of 2021 and UUPA, indicating a violation of the principle of lex superior derogate legi inferiori. This creates juridical problems with cultivation rights over management rights, and can result in legal uncertainty for holders of cultivation rights over management rights.